I my zmarchwystaniemy [Bożonarodzeniowa karta okolicznościowa] . We also shall resurrect. Christmas greeting card - Solidarność Walcząca. (Solidarność Walcząca)
B&w print on white paper, with undivided back. Christmas greeting card contains a graphic image which represents Jesus with hand in the gesture of victory and text with greetings from Fighting Solidarity.